Control System for Adjusting the Brightness Level with PWM Technique Using Visual Net Microcontroller-Based - Dedi Setiawan; Ishak Ishak; Muhammad Ardiansyah Sembiring (Journal of Robotics and Control (JRC), 2020)
The lamp is an artificial source of light that is produced by channelling electric current through the filament which then heats up and produces light. Eye health experts believe that the ideal brightness of a lamp depends on ambient light or ambient light. The rule must ensure that the brightness of the lights must be equivalent to the light around. That way the light from the lights and surroundings will blend and not make the eyes have to work harder. To overcome this problem a control system can be created by implementing the pulse width modulation (PWM) technique that can control the brightness of the lights manually using a visual net application. Utilization of a microcontroller as a control center in controlling the brightness level of the lamp using the type of microcontroller avr16 by displaying the PWM value on the form design on the visual net. Thus setting the level of light brightness to be ideal in the conditions we want.